The higher education system and the labor market: state and ways of effective cooperation (International relations and international law Journal, 2016)
Trends in the development of Kazakhstan’s society is natural show ever-increasing znachenii education and as a tool for the creation of the intellectual potential of the state, and as a resource that provides vital blago¬poluchie citizens, and as a factor konkurentospo sobnosti individual organizations and the state in general. The education system is transformed into a priority, leading area of social and economic policy, and becomes indikatorom and catalyst for the development of the country. One of the ways to solve the problem – Update modular educational programs in the context of strengthening the practical relevance of the acquired knowledge and skills with the participation of employers in the creation of standards of higher education in the teaching of individual courses tailored to the needs of the labor market. We should create such conditions of remuneration for which the university would work very highly qualified. Interaction between education and business, identify ways to improve the relationship of the market of higher education and the labor market has become a key indicator of the effectiveness of higher education and training quality.
Keywords: the education system; labor market; Local Integration; strategy; innovation development